How to speak "geocentric" in an "egocentric" language: A multimodal study among Ngigua-Spanish bilinguals and Spanish monolinguals in a rural community of Mexico. (July 2019) - Calderón, Eréndira; De Pascale, Stefano; Adamou, Evangelia
Abstract: It has recently been shown that individuals residing in rural, indigenous communities rely on geocentric conceptualizations of space, e.g., north/south/east/west, even after they have shifted to a language that is known to favour egocentric conceptualizations, e.g., right/left. In this paper we explore how this combination works in practice by conducting a study in a previously non-investigated indigenous community of Mexico, the Ngiguas. We used a verbal localization task for community–scale relations. We filmed the responses of early bilinguals in Ngigua (Otomanguean) and in Spanish as well as of a control group of Spanish monolinguals from the same rural community. Statistical analysis of speech and co-speech gestures reveals that bilinguals favour geocentric gestures and direct pointing in both languages, associating them with topological and deictic terms. Against our predictions, Spanish monolinguals also use high rates of geocentric gestures that they frequently combine with cardinal terms. In sum, the Ngigua data show that geocentric conceptualizations can be transmitted to monolingual generations via co-speech gestures, including in a language where egocentric conceptualizations prevail in other settings. Highlights: A study of speech and co-speech gesture in a non-investigated population of bilinguals. Conceptual convergence among the bilinguals based on the geocentric conceptualizations of the attrited language. Geocentric linguistic conceptualizations are transmitted to monolingual speakers. A stable relation to the environment may facilitate maintenance of geocentric conceptualizations. Geocentric linguistic conceptualizations are resilient to literacy.